Relationships of triglyceride–glucose index and body mass index with 5-year all-cause mortality in patients with diabetes and comorbid hypertension: Evidence from two prospective cohort studies - Yilu Liu; Hongzhao You; Yingxuan Zhu; Fang Luo; Yanyan Zhao; Dingyue Zhang; Ying Xiao; Shijie You; Rui Zhang; Yingdong Han; Jing Li; Shouling Wu; et al. (Journal of Clinical & Translational Endocrinology)
Aims: To characterize the complex relationships of body mass index (BMI) and triglyceride–glucose index (TyG) with 5-year all-cause mortality in patients with diabetes mellitus and comorbid hypertension. Methods: Overall, 5,728 patients from the 1999–2014 US National Health and Nutrition Examination Survey (NHANES) cycles and 3,456 from the 2005–2010 China Kailuan cycles were included. TyG was calculated as the logarithmic product of the fasting triglyceride and glucose concentrations. Results: The prevalence of 5-year all-cause mortality was 8.4 % in the NHANES population and 9.2 % in the Kailuan cohort. TyG mediated the association between BMI and all-cause mortality, being responsible for 38.4 % in the NHANES database and 41.6 % in the Kailuan cohort. Significant multiplicative effects were identified between TyG and BMI, which were closer for patients with high BMI. When stratified by BMI and TyG, high-risk subgroups were identified and had higher risks of all-cause mortality than the intermediate- and low-risk subgroups (both log-rank P < 0.001). Conclusions: TyG mediated a considerable proportion of the effect of BMI on all-cause mortality in patients with diabetes and hypertension. The combination of BMI and TyG could be useful for the risk stratification of all-cause mortality. Measures aimed at weight loss might reduce the all-cause mortality risk associated with insulin resistance.